An Introduction to Sustainable Development - Elliott, Jennifer A. , 1962- (Routledge perspectives on development, 2013)
This fourth edition has been comprehensively rewritten and updated to provide a concise, well illustrated and accessible introduction to the characteristics, challenges and opportunities of sustainable development with particular reference to developing countries. The contested nature of sustainable development is explored through a detailed consideration of changing ideas and practices within environmentalism and development thinking.The text identifies the different actors involved